To Become or Not to Become Tumorigenic: Subventricular Zone Versus Hippocampal Neural Stem Cells - Fontán-Lozano, Ángela; Morcuende, Sara; Davis-López de Carrizosa, Mª América; Benítez-Temiño, Beatriz; Mejías, Rebeca; Matarredona, Esperanza R. (Frontiers in Oncology, 2020)
Neural stem cells (NSCs) persist in the adult mammalian brain in two neurogenic regions: the subventricular zone lining the lateral ventricles and the dentate gyrus of the hippocampus. Compelling evidence suggests that NSCs of the subventricular zone could be the cell type of origin of glioblastoma, the most devastating brain tumor. Studies in glioblastoma patients revealed that NSCs of the tumor-free subventricular zone, harbor cancer-driver mutations that were found in the tumor cells but were not present in normal cortical tissue. Endogenous mutagenesis can also take place in hippocampal NSCs. However, to date, no conclusive studies have linked hippocampal mutations with glioblastoma development. In addition, glioblastoma cells often invade or are closely located to the subventricular zone, whereas they do not tend to infiltrate into the hippocampus. In this review we will analyse possible causes by which subventricular zone NSCs might be more susceptible to malignant transformation than their hippocampal counterparts. Cellular and molecular differences between the two neurogenic niches, as well as genotypic and phenotypic characteristics of their respective NSCs will be discussed regarding why the cell type originating glioblastoma brain tumors has been linked mainly to subventricular zone, but not to hippocampal NSCs.